Christos Tsiolkas’s The Slap Multiculturalism in Australia Now - Muljadi, Hianly (Lingual Journal of Language and Culture; Vol 10 No 2 (2020): Lingual: Journal of Language and CultureDO - 10.24843/LJLC.2020.v10.i02.p08, 2020)
This study focuses on the use of narrative techniques, especially point of view, in a novel entitled The Slap written by an Australian author, Christos Tsiolkas. This novel begins with a barbeque party hosted by a couple in a suburban Melbourne. The party is attended by many of their friends, families and co-workers who come from many different ethnic backgrounds, mostly immigrants or immigrant descents in Australia. The story takes an interesting turn when a man slaps an unruly boy who is not his own. The boy’s parents become so furious and decide to report the incident to the police. The story then continues with the revelation on how the case goes. What is special about this novel is that the aftermath of the incident is written in multiple chapters, narrated by a different character for each chapter. Readers will be able to see what happen after the incident through the eyes of each character who not only talk about the incident but inform the readers also about their life and the people around them. This is very interesting considering all the characters come from different ethnics; Greek, Indian, Jew, and British Australian. Christos Tsiolkas claimed that he wanted to show the real Australia which is not often represented in other novels through this novel and he has chosen to use the 3 rd person limited point of view as a means to deliver his message. At the end of the research it can be concluded that there is a shift in position between the white Australians and immigrants or immigrant descent nowadays in terms of superiority and inferiority.   Keywords : narrative technique, point of view, multiculturalism, immigrant, white Australians.